Self-supporting sandwich-structured Co–Pt–Co/CC electrocatalysts for high effective hydrogen production by electrolysis of water in alkaline solution. (12th January 2023) - Liu, Wenqian; Tang, Yang; Liu, Fan; Gao, Li; Yang, Daxiang; Yang, Jingang; Bao, Shu-Juan
Abstract: Trace precious metal modifying inexpensive transition metal catalyst is an effective method to optimize the activity, stability and cost of hydrogen evolution catalysts. In this feature work, self-supporting sandwich structured Co–Pt–Co/CC sheets were assembled on a carbon cloth (CC) by a simple electrodeposition/chemical displacement alternate growth method. Surprisingly, only 2.1 wt % Pt sandwich layer greatly improved the electrochemical activity of Co–Pt–Co/CC, which delivered a current density of 10 mA cm −2 at an overpotential as low as 46 mV. Importantly, its overpotential is almost 6 times lower than that of Co/CC, and is comparable to that of Pt–Co/CC. After well-tuning the sandwich layer, the optimized Co–Pt–Co/CC exhibited a higher current density and better long-term durability compared with Pt–Co/CC and Co/CC, which can be attributed to the unique tissue-structure and electronic structure optimization of the Co–Pt–Co/CC by the Pt sandwich layer. Graphical abstract: Image 1 Highlights: Doping trace Pt into the sandwich-like structured Co–Pt–Co/CC can significantly improve its HER performance. The sandwich like self-supporting electrode can easily be prepared by alternating electrodeposition and impregnation. The good hydrophilicity of Co–Pt–Co/CC surface can rapidly divert H2 gas bubbles.